TGA/Chemometric Test Is Able to Detect the Presence of a Rare Hemoglobin Variant Hb Bibba - Risoluti, Roberta; Caprari, Patrizia; Gullifa, Giuseppina; Diana, Loretta; Luciani, Matteo; Amato, Antonio; Materazzi, Stefano (Frontiers in Molecular Biosciences, 2019)
In this study the TGA/Chemometric test was applied for diagnosis of a case of congenital hemolytic anemia for which the common first level diagnostic tests were not able to find the erythrocyte congenital defect. A 6 years old girl presented chronic hemolytic anemia characterized by hyperbilirubinemia, increased spleen, negative Coombs tests, normal hemoglobin values, decreased mean corpuscolar volume (MCV), increased red cell distribution width (RDW), reticulocytes and lactate dehydrogenase (LDH) and altered erythrocyte morphology (ovalocytes, spherocytes and rare schizocytes). The diagnostic protocols for differential diagnosis of hereditary hemolytic anemia were carried out by the investigation of the congenital hemolytic anemias due to defects of membrane proteins and the most common erythrocyte enzymes, but no defect was found. The TGA/Chemometric test was applied and the PLS-DA model of prediction was used to process results. The thermogravimetric profile of the patient was very distinct from those of healthy subjects and comparable with those of thalassemia patients. The classification model applied to the patient identified a chronic hemolytic anemia due to a hemoglobin defect and the molecular characterization confirmed the TGA/Chemometrics results, demonstrating the presence of a very rare hemoglobin variant Hb Bibba (α2136(H19)Leu→Proβ2). In conclusion the TGA/Chemometric test proved to be a promising tool for the screening of the hemoglobin defects, in a short time and at low cost, of this case of congenital hemolytic anemia of difficult diagnosis. This method results particularly suitable in pediatric patients as it requires small sample volumes and is able to characterize patients subjected to transfusion.